Bauran Pemasaran Kepuasan Dan Loyalitas Pelanggan Benih Kelapa Sawit PT Socfin Indonesia - Sri Ariani Safitri; Suharno Suharno; Anna Fariyanti (Fakultas Ekonomi dan Bisnis, Universitas Tarumanagara, 2017)
Along with the increasing demand of palm oil seedtrigger an increased numberof seed producers of palm oil in Indonesia. Under conditions of tight competition, PTSocfin Indonesia (Socfindo) as one of the producers of palm oil seedneeds to evaluate theperformance of the marketing mix (product, price, place and promotion) through customersatisfaction and loyalty. This study aimed to analyze the influence of marketing mixtowards customer satisfaction and loyalty as well as to analyze the level of satisfaction andloyalty customer palm oil seed ofPT Socfindo. Thecollection of data through the 30respondent companies. Data analysis methods used Structural Equation Model PartialLeast Square (SEM PLS). Analysis results showed thatthe the product variables have asignificant influence on customer satisfaction and loyalty, while the variables of price,place and promotion does not have a significant influence in shaping customer satisfactionand loyalty. In addition, the calculationresults Customer Satisfaction Index (CSI),customer satisfaction index palm oil seed PT Socfindo which can be categorized as verysatisfied and calculating results Customer Loyalty Index (CLI), an index of customerloyalty palm oil seed PT Socfindo which can be categorized loyal.